The lotus painting on the manuscripts: a study of pictographic punctuation marks in Dunhuang manuscripts - Wu, Shaowei (Studies in Chinese Religions, 2024)
In Dunhuang Buddhist manuscripts, various punctuation marks, some intuitive and figurative, were used by people of the time. These marks serve both philological and iconographic functions, closely related to the daily lives of their creators. They can be categorized into two types based on religious implications: one without obvious Buddhist characteristics and the other with evident Buddhist elements. The latter can further be divided into two subcategories related to Esoteric Buddhism: closely related and not closely related. Though not professional artworks, these symbols reflect the artistic abilities of ordinary monks in daily practice. Their creation and use express monks’ beliefs and tastes and are integral to the monastic community’s knowledge construction in the medieval period.